2022
DOI: 10.1038/s41467-022-30712-x
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota-bile acid axis links the positive association between chronic insomnia and cardiometabolic diseases

Abstract: Evidence from human cohorts indicates that chronic insomnia is associated with higher risk of cardiometabolic diseases (CMD), yet whether gut microbiota plays a role is unclear. Here, in a longitudinal cohort (n = 1809), we find that the gut microbiota-bile acid axis may link the positive association between chronic insomnia and CMD. Ruminococcaceae UCG-002 and Ruminococcaceae UCG-003 are the main genera mediating the positive association between chronic insomnia and CMD. These results are also observed in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 80 publications
1
45
2
Order By: Relevance
“…Secondary bile acids such as DCA and LCA are positively correlated with the abundance of members of the Firmicutes such as Clostridiales, Enterococcaceae, Eubacteriaceae, Lachnospiraceae, and Ruminococcaceae in the gut and negatively correlated with the abundance of Enterococcus, Lactobacillus, and others (Connors et al, 2020;Li et al, 2021;Yang et al, 2021). Jiang et al found that Ruminococcaceae UCG-002 and UCG-003 are positively correlated with secondary bile acids (IsoLCA, LCA and UDCA) and negatively correlated with primary bile acids (MCA and NorCA) in chronic insomnia and cardiometabolic disease (Jiang et al, 2022). In addition, Wei et al, in a study of obesity susceptibility, found that Clostridium scindens is positively correlated with LCA, DCA, and UDCA and that Clostridium hylemonae is significantly positively correlated with UDCA (Wei et al, 2020).…”
Section: The Gut Microbiota-bile Acid Axismentioning
confidence: 99%
See 3 more Smart Citations
“…Secondary bile acids such as DCA and LCA are positively correlated with the abundance of members of the Firmicutes such as Clostridiales, Enterococcaceae, Eubacteriaceae, Lachnospiraceae, and Ruminococcaceae in the gut and negatively correlated with the abundance of Enterococcus, Lactobacillus, and others (Connors et al, 2020;Li et al, 2021;Yang et al, 2021). Jiang et al found that Ruminococcaceae UCG-002 and UCG-003 are positively correlated with secondary bile acids (IsoLCA, LCA and UDCA) and negatively correlated with primary bile acids (MCA and NorCA) in chronic insomnia and cardiometabolic disease (Jiang et al, 2022). In addition, Wei et al, in a study of obesity susceptibility, found that Clostridium scindens is positively correlated with LCA, DCA, and UDCA and that Clostridium hylemonae is significantly positively correlated with UDCA (Wei et al, 2020).…”
Section: The Gut Microbiota-bile Acid Axismentioning
confidence: 99%
“…The interaction between the gut microbiota and bile acids is complex and bidirectional in the host, known as the gut microbiota–bile acid axis ( Hou et al., 2021 ; Wu et al., 2021b ; Jiang et al., 2022 ). The gut microbiota can transform and modify bile acids, influence bile acid production, and alter bile acid receptor signaling.…”
Section: The Gut Microbiota–bile Acid Axis In Liver Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…And the acute circadian rhythm disturbance caused by sleep-wake shifts affect the human gut microbiota (75), especially the functional profiles of gut microbes and interactions among them. Thus, the gut microbiome is a potential target for reducing the impact of chronic insomnia on cardiometabolic health (76). Due to a causal relationship between the gut microbiome and hypertension (77), the former may be a target for treatment of OSA-related and other typical hypertension.…”
Section: Mechanisms Mediated By Sleep and Microbiomementioning
confidence: 99%